The Kinetics and Mechanism of the Pyrolysis of Manganese and Manganese Suicide CVD Precursors - Russell, Douglas K.; Davidson, Iain M. T.; Ellis, Andrew M.; Mills, Graham P.; Pennington, Mark; Povey, Ian M.; Saydam, Sinan (Wiley-VCH Verlag, 1998)
The gas-phase pyrolysis of methyl pentacarbonyl manganese and acetyl pentacarbonyl manganese, both alone and in the presence of trimethyl silane, has been investigated using stirred flow reactor kinetic measurements and IR laser powered pyrolysis, together with electron spin resonance (ESR) detection of radical intermediates. For methyl pentacarbonyl manganese alone, all observations support a mechanism initiated by methyl-manganese bond homolysis, whereas the initial step in the acetyl compound involves CO loss and methyl migration. The addition of trimethylsilane sensitizes decomposition of MeMn(CO)5, yielding methane and trimethylsilyl pentacarbonyl manganese; on the other hand, Me3SiH has little effect on the rate of decomposition of MeCOMn(CO)5. A mechanism based on methyl migration is proposed to account for these observations.
Keywords: Kinetics; Manganese; Mechanism; Pyrolysis; Suicide